Immune signaling pathways in the endoparasitoid, Pteromalus puparum. Issue 2 (9th October 2019) - Yang, Lei; Wang, Jiale; Jin, Hongxia; Fang, Qi; Yan, Zhichao; Lin, Zhe; Zou, Zhen; Song, Qisheng; Stanley, David; Ye, Gongyin
Abstract: Parasitoids serve as effective biocontrol agents for agricultural pests. However, they face constant challenges from host immune defense and numerous pathogens and must develop potent immune defense against these threats. Despite the recent advances in innate immunity, little is known about the immunological mechanisms of parasitoids. Here, we identified and characterized potential immune‐related genes of the endoparasitoid, Pteromalus puparum, which act in regulating populations of some members of the Pieridae. We identified 216 immune‐related genes based on interrogating the P. puparum genome and transcriptome databases. We categorized the cognate gene products into recognition molecules, signal moieties and effector proteins operating in four pathways, Toll, IMD, JAK/STAT, and JNK. Comparative analyses of immune‐related genes from seven insect species indicate that recognition molecules and effector proteins are more expanded and diversified than signaling genes in these signal pathways. There are common 1:1 orthologs between the endoparasitoid P. puparum and its relative, the ectoparasitoid Nasonia vitripennis . The developmental expression profiles of immune genes randomly selected from the transcriptome analysis were verified by a quantitative polymerase chain reaction. Our work provides comprehensive analyses of P. puparum immune genes, some of which may be exploited in advancing parasitoid‐based biocontrol technologies. Abstract : An overview of Pteromalus puparum immune‐related genes functions in melanotic processes and four pathways, Toll, IMD, JAK/STAT, and JNK. Research Highlights: A total of 216 immune‐related genes of Pteromalus puparum were identified. Comparative analyses of immune‐related genes between P. puparum and six other insect species indicate recognition molecules and effectors are more expanded and diversified. Results showed common 1:1 orthologs between the endoparasitoid P. puparum and its relative, the ectoparasitoid Nasonia vitripennis .